2005
DOI: 10.1111/j.1601-183x.2005.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic contribution to canine personality

Abstract: The domestic dog may be exceptionally well suited for behavioral genetic studies owing to its population history and the striking behavior differences among breeds.To explore to what extent and how behavioral traits are transmitted between generations, heritabilities and genetic correlations for behavioral traits were estimated in a cohort containing over 10 000 behaviorally tested German shepherd and Rottweiler dogs. In both breeds, the pattern of co-inheritance was found to be similar for the 16 examined beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 42 publications
(64 reference statements)
3
69
1
1
Order By: Relevance
“…This assessment measures the dog's sociability, playfulness, fearlessness and boldness, through the use of multiple behavioural assessments (Svartberg, 2005). These results are, however, greatly influenced by external factors, such as the scoring judge (Ruefenacht et al, 2002;Saetre et al, 2006).…”
Section: Selecting Detection Dogsmentioning
confidence: 99%
“…This assessment measures the dog's sociability, playfulness, fearlessness and boldness, through the use of multiple behavioural assessments (Svartberg, 2005). These results are, however, greatly influenced by external factors, such as the scoring judge (Ruefenacht et al, 2002;Saetre et al, 2006).…”
Section: Selecting Detection Dogsmentioning
confidence: 99%
“…They showed that more trainable breeds live longer than disobedient breeds and that aggressive breeds have higher levels of energy expenditure than unaggressive breeds. Because behavioural differences among dog breeds have a genetic basis (Saetre et al 2006) and can be regarded as remnants from past selection targeted at personality (Svartberg 2006), the genetic component underlying these correlations is presumably high.…”
Section: Trait Interactions Contributingmentioning
confidence: 99%
“…Liimatainen et al (2008) presented somewhat lower heritability estimates (0.04-0.13), in a study based on 2327 Rottweilers tested in an official behaviour test in Finland. Saetre et al (2006) analysed DMA results from German Shepherd Dogs and Rottweilers. Their heritability estimates for the items were quite similar for the two breeds and varied between 0.04 and 0.19.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…For example, measurements can be made in competitions or field trials (e.g., Karjalainen et al, 1996;Hoffmann et al, 2002;Correau & Langlois, 2005), when the dog is exposed to a standardized test battery (e.g., Wilsson & Sundgren, 1997;Ruefenacht et al, 2002;Saetre et al, 2006), or by observing the dog in everyday life, during training or while walking in different environments (e.g., Murphy, 1997;Schiefelbein, 2012Schiefelbein, , 2013. The judges can be extensively trained for the task (e.g., Ruefenacht et al, 2002;Saetre et al, 2006), persons regarded as skilful and competent but without formal training, or, if a dog owner questionnaire is used, the dog owners (e.g., Liinamo et al, 2007). The measurements can be more or less objective, and the ratings can refer to behaviours displayed in a specific situation or to an overall interpretation indicating the degree of expression of pre-defined traits (Wilsson & Sinn, 2012).…”
Section: Main Issuesmentioning
confidence: 99%